Taxonomical study on the Vetigastropoda (Mollusca) from Canopus Bank, NE Brazil, with further remarks on their distribution along the Western Atlantic - Cavallari, Daniel Caracanhas (2017)
A taxonomic revision of 29 species distributed in 12 vetigastropod families collected in a 60-260 m depth range at Canopus Bank, a seamount off NE Brazil, is performed based on detailed shell morphology. Their distribution and bathymetric ranges are re-examined based on specimens from Canopus and the MZSP collection. Three possibly new species are revealed and tentatively described: Arene aff. brareus can be distinguished by a large shell for the genus; sculpture consisting of spiral cords ornamented by large, semi-hollow, scale-like spines; cords separated by equally wide, deep interspaces and thin axial growth lines more visible in the interspaces; protoconch sculptured by small, subsutural axial lamellae; and color ranging from white to intense reddish, darker on spiral cords, and lighter at the base, with a yellow apex. Parviturbo aff. tuberculosus can be told apart from local congeners by its slightly taller than wide shell, which is profusely sculptured by a reticulate pattern of equally strong axial ribs and spiral cords, with angular nodules at the intersections. Calliostoma sp.1 shows no close affinities with any other local congener and is characterized by a small shells with convex whorls and a large, rounded apex; ivory white ground color with honey yellow apex and spiral cords; sculpture consisting of 4-6 narrow, nodulous spiral cords per whorl; suture marked by a suprasutural cord; inflated and mostly smooth base; narrow, shallow, and axially sculptured umbilicus. Moreover, three species have their distributions expanded northward from SE to NE Brazilian waters: Emarginula suspira Simone & Cunha, 2014, Hemimarginula hemitoma Simone & Cunha, 2014, and Homalopoma boffi Marini, 1975. Three species have their northern range limit expanded from Bahia state to Ceará state: Arene flexispina Leal & Coelho, 1985 and Turbo heisei Prado, 1999; a single NE Brazilian species is newly reported from northern waters: Haplocochlias risoneideneryae Barros, Santos, Santos, Cabral & Acioli, 2002; and another species, previously known only from Pernambuco state, is newly reported from Ceará state, also in NE Brazil: Solariella quinni Barros & Pereira, 2008. Two Caribbean species are firstly reported in the SW Atlantic: Dentistyla dentifera (Dall, 1889) and Gaza cf. fischeri (Dall, 1889); and a species previously reported from the Venezuelan shelf is firstly recorded in Brazilian waters: Parviturbo annejoffeae Rubio, Rolán & Lee, 2015. The bathymetric ranges of 11 species are expanded. High-resolution photographs of the type specimens, SEM images, and comparisons with local congeners are also provided